Structure changes in zirconium after plasma treatment and high-temperature annealing in air atmosphere - Shymanski, Vitali I.; Abramava, Viktorya V.; Astashynski, Valiantsin M. (Journal of the Belarusian State University. Physics, 2025)
In order to test the possibility of increasing the corrosion resistance of zirconium alloys used as structural materials in nuclear power, the stability of the structure and phase state of zirconium subjected to high-energy plasma exposure and then isothermal annealing in an air atmosphere was investigated. The zirconium samples were processed by pulsed compression plasma flows in an atmosphere of residual gas (nitrogen) with an absorbed energy density that ensured melting of the surface layer and subsequent rapid crystallisation. The result of plasma exposure was the formation of a dispersed grain structure, accompanied by the growth of a thin layer of zirconium nitride (ZrN) and a solid solution of nitrogen in the crystal lattice of the low-temperature phase of zirconium (α-Zr(N)) on the surface. The thermal stability of modified zirconium was studied by isothermal annealing in an open-air atmosphere at a temperature of 350 ℃ for 100 h. Using scanning electron microscopy and X-ray diffraction analysis, diffusion saturation of the near-surface layer of zirconium samples with oxygen atoms leading to the formation of a monoclinic modification of zirconium dioxide (m-ZrO2) and an interstitial solid solution (α-Zr(O)) has been found. It is shown that modification of the structure of the zirconium surface layer by preliminary plasma treatment prevents the formation of m-ZrO2 zirconium dioxide, while increasing the region of existence of the α-Zr(O) solid solution. The formed zirconium nitride layer acts as a barrier to the diffusion penetration of oxygen. However, the decomposition of zirconium nitride, which occurs in the solid phase, leads to an increase in the number of vacant positions in the crystal lattice, facilitating the formation of the α-Zr(O) solid solution. The found peculiarities of structure changes in zirconium after high-temperature annealing make it possible to reduce the weight gain of samples during long-term oxidation in an air atmosphere.